Book review: The mixing of magmas. Field evidence, numerical models, experiments, by Diego Perugini, 2021. Advances in Volcanology, Springer, Switzerland; 162 pages; eBook price 85.89 EUR, ISBN978-3-030-81810-1 - Scarpati, Claudio (Geologos, 2023)
Not provided.